Rekonstruksi Nilai Kemandirian Abdullah bin Umi Maktum dalam Konteks Pendidikan Inklusif bagi Anak Tunanetra - mastur (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2026)
ABSTRACT character development among visually impaired learners within inclusive and special education settings. This study aims to examine the values of independence embodied by Abdullah bin Umi Maktum and to analyze their relevance to the educational experiences of visually impaired students at Boyolali State Special School. The research adopts a qualitative literature review approach supported by a simple interview with a visually impaired student to enrich the analysis with practical insights and lived experiences. The findings indicate that Abdullah bin Umi Maktum exemplifies perseverance, self-confidence, resilience, and active engagement in social life despite physical limitations. These values provide an inspiring and contextual model for fostering independence among visually impaired children. The study further highlights that integrating the exemplary values of Abdullah bin Umi Maktum into educational practices and learning materials can contribute to strengthening students’ self-reliance, enhancing their confidence, and encouraging meaningful social participation. Therefore, his legacy offers a relevant foundation for developing character-based educational programs that support the empowerment of visually impaired learners in Indonesia. Keywords: Role Model, Abdullah bin Umi Maktum, Independence, Visually Impaired Students, Special Education.